CAM OPERATED POWER HAMMER - Siddhesh Santosh Kumavat; Mahesh Suresh Ranbagul; Nilesh Pandurang Vekhande; Omkar Sanjay Kaminwar; Prof. Asmit Manohar Burud (International Engineering Journal For Research & Development, 2021)
In several industries varied styles of machines and instrumentation are used for varied operations like formation, hammering, cutting etc. however totally different issues like low power offer, less man power and conjointly significant arduous workforce, safety etc. This comes relates to operation performed by this could be achieved by either mistreatment motor power or by manually by suggests that of merely rotating a hand lever hooked up to the shaft and hammer action may be provided. If there's smart power offer it may be run mechanically. For automatic operation A.C. motor is provided. Chain drive, belt drive, governor are provided for speed management functions in order that the appropriate speed may be achieved. At last when there is no electrical power offered is there the advance cam operated hammer may used as manually by merely rotating the hand lever. Conjointly the handling is straightforward and maintenance is simple of the project.